Lessons for human survival in a world without ecological templates: what can we learn from small-scale societies? - Roope O. Kaaronen (Resilience Alliance, 2021)
Historical records are incomplete templates for preparing for an uncertain future. The global utility of past ecological knowledge for present/future purposes is questioned as we move from Holocene to Anthropocene. To increase the adaptive capacity of today's societies, generalizable strategies must be identified for coping with uncertainty over a wide range of conditions and contingencies. We identify two key principles that increase adaptive capacities: diversification and precautionary heuristics. These sharply contrast with the present global state represented by the global production ecosystem characterized by: (1) homogenization and simplification of cultural practices and resource bases; (2) increased global connectivity and forced dissolution of cultural borders; and (3) centralization and intensification of modes of resource production and extraction. We highlight that responses of smaller-scale societies to risks and uncertainties are in many cases emulated by professionals in the high reliability management in today's critical infrastructures. This provides a modern template for managing unpredictability in the Anthropocene.